The Role of Feedback in Motivating EFL Students in Vocational High School: A Qualitative Analysis of Students’ Perceptions - Nurhayati, Nunung; Apoko, Tri Wintolo (Universitas Pahlawan Tuanku Tambusai, 2024)
Feedback informs students about their language performance, assisting them in grasping their abilities as well as opportunities for improvement. The importance of feedback in educational settings is well established, with research highlighting its ability to guide learners, build up positive behaviours, and create a supportive learning environment. The purpose of this study is to find out how feedback affects the motivation of EFL students in vocational high schools. The method of this research was a descriptive qualitative design. The results show that feedback in English language learning serves as a catalyst for students' self-improvement and motivation. Understanding individual preferences, providing personalized feedback, and creating a supportive learning environment are essential for maximizing the impact of feedback on students' learning outcomes. While responses to feedback may vary among individuals, there is a common theme of dedication to continuous improvement and a willingness to overcome challenges. Positive and constructive feedback generally leads to increased motivation, fostering a growth mindset among students.